Crystallization of Short‐Chain Amylose: Effect of the Precipitant. (3rd April 2019) - Huang, Zhaohua; Zeng, Zhilu; Gao, Yifang; Liu, Chengmei; Wu, Jianyong; Hu, Xiuting
Abstract : The effects of ethanol and polyethylene glycol (PEG) on crystallization of short‐chain amylose are investigated. In the absence of precipitants, the yield of short‐chain amylose precipitate is 38.8%, while the presence of ethanol and PEG increases the yield to 45.1% and 54.7%, respectively. Moreover, the crystallinity of the precipitate obtained without the precipitants is 45.4%, while the presence of ethanol and PEG increases the crystallinity to 50.4% and 48.6%, respectively. In the absence of precipitants, the precipitate shows B‐type crystallinity and is spherical with the size <1 µm. In the presence of ethanol, the precipitate displays A‐type crystallinity and an elongated platelet shape with the length >1 µm. The precipitate obtained in the presence of PEG is also B‐type and spherical but is smaller than the precipitate obtained in the absence of precipitants. These results suggest that ethanol and PEG significantly affect crystallization of short‐chain amylose in different ways. Abstract : The effect of PEG on the crystallization of short amylose is investigated and compared with the effect of ethanol. Without precipitants, the precipitate shows B‐type crystallinity and is spherical. Addition of PEG did not change crystal type and shape but decreased the size, while the presence of ethanol induced an A type precipitate with an elongated platelet shape.